How to pick the right candidates for interview. (2nd February 2020) - Foran, Kaley
Abstract : Interview shortlisting is a vital stage of recruitment. Kaley Foran looks at how to ensure your school's shortlisting process is fair and can stand up to scrutiny if a decision is challenged